Screening for Anxiety and Depression in Children with Congenital Adrenal Hyperplasia - Marianne Jacob; Karen Lin-Su; Corinne Catarozoli; Charlene Thomas; Dix Poppas; Oksana Lekarev (Galenos Yayincilik, 2023)
INTRODUCTION: Congenital adrenal hyperplasia (CAH) is an inherited condition in which individuals require multiple daily doses of medication and are at risk for life-threatening adrenal crisis. The chronic nature and severity of CAH place children at risk for psychiatric morbidity. The aim was to assess the degree of anxiety and depressive symptoms in children with CAH. METHODS: A cross-sectional cohort study of children (7-17 years) with CAH and their caregivers were recruited between May and December 2021. Children with hypothyroidism (HT) and their caregivers served as unaffected controls. Validated mental health questionnaires [Children's Depression Inventory 2 Self Report-Short (CDI-2), Screen for Child Anxiety Related Disorders (SCARED), Patient Health Questionnaire modified for Adolescents (PHQ-A); self and proxy] were completed by participants at one clinic visit. Higher scores indicated greater symptoms of anxiety and depression. RESULTS: A total of 60 children and 56 parents participated. Among the children 34 had CAH (68% female, mean age 11.41±2.5, CAH duration 8.5±4.1) and 26 had HT (73% female, mean age 12.7±2.9 years, HT duration 6.0±4.2 years). There was no increase in anxiety and depression symptoms in children with CAH compared to controls. In sub-analyses, children with CAH and controls reported a greater number of anxiety and depression symptoms than their caregivers on the SCARED and CDI-2, respectively. There was no association between adrenal control and the degree of anxiety or depression symptoms. DISCUSSION AND CONCLUSION: Children with CAH do not have more symptoms of anxiety or depression compared to controls. Child and caregiver-proxy responses lack agreement, suggesting that children with CAH may continue to benefit from routine mental health evaluation, regardless of voiced caregiver concern.